An easy 'Filter-and-Separate' method for enantioselective separation and chiral sensing of substrates using a biomimetic homochiral polymer1. Issue 43 (28th May 2015) - Senthilkumar, T.; Asha, S. K.
<x xml:space="preserve">Abstract</x> A new homochiral polyfluorene appended with l-glutamic acid demonstrated successful heterogeneous enatioselective separation of a wide variety of enantiomers from their aqueous racemic mixtures by selective uptake of l-enantiomer into the polymer.